The medium-term budgetary framework under Organic Law No. 18-15 on Finance Acts - Nawal, Sabeg; Nouh, Ferroudji; Ayoub, Agoudjil; Aouda, Bouadma (The International tax journal, 2025)
This paper aims to shed light on one of the key pillars of budgetary reform in Algeria under Organic Law No. 18-15 of 2 September 2018 on Finance Acts-namely, the Medium-Term Budgetary Framework (MTBF), including its design and preparation procedures. The study concludes that the MTBF serves as a strategic instrument reflecting the government’s overarching fiscal orientations and as a mechanism for aligning the state’s general budget with established policy priorities. It provides public managers with a multi-year outlook on expected public revenues and expenditures, thereby enhancing fiscal planning and predictability. Nevertheless, significant ambiguity remains—particularly regarding the practical modalities for programming multi-year budgets within the MTBF. Consequently, the Algerian Ministry of Finance is urged to provide clearer operational guidance to budget managers and to simplify the legal and regulatory provisions governing this framework to avoid unnecessary complexity.